Correlation of Breastfeeding and Parenting with Early Childhood’s Emotional Development - Nurhamidi Nurhamidi; Rizky Rindu Bajuri (Pusat Unggulan IPTEK POLTEKKES KEMENKES Malang, 2022)
The mental emotional development children is the interaction process of the maturation of the child physiology and psychological organs to process and control emotions. The study aimed to found out the correlation between exclusive breastfeeding and parenting with the mental emotional development of early childhood in the working area of Puskesmas Guntung Manggis in 2021. The study is an observational analytic study with a cross sectional design. The sample of the study was 92 samples of early age are 3 until 6 years in the working area of Puskesmas Guntung Manggis, it was determined by a simple random sampling technique. The data analysis was conducted by the Rank Spearman correlation. Based on the results shows that there is a relationship between exclusive breastfeeding with value is 0.0 and parenting with value is 0.0 with the mental emotional development of early childhood in the working area of Puskesmas Guntung Manggis. It is expected for the mothers to provide exclusive breastfeeding and change parenting to positive parenting to support optimal mental emotional development of children.